Pyrido-Fused Deazapurine Bases: Synthesis and Glycosylation of 4-Substituted 9H-Pyrido[2',3':4,5]- and Pyrido[4',3':4,5]pyrrolo[2,3-d]pyrimidines - Veselovská, Lucia; Pohl, Radek; Tloušt Ová, Eva; Gurská, Soňa; Džubák, Petr; Hajdúch, Marián; Hocek, Michal (ACS omega, 2020)
Two isomeric sets of 4-substituted pyridopyrrolopyrimidine nucleobases were prepared through nucleophilic substitutions or cross-coupling reactions of 4-chloropyridopyrrolopyrimidines. The corresponding 4-amino-pyridopyrrolopyrimidines were glycosylated with 5-O-tritylribose using the modified Mitsunobu protocol. Several examples of the title heterocycles showed blue or green fluorescence. Testing of the pyridopyrrolopyrimidine nucleobases for the cytotoxic effect revealed micromolar activity of 4-benzofuryl derivatives in both series, preferentially in multidrug-resistant cancers.